Positional cloning of a peanut CC-NBS-LRR gene, AhRRS6, confers resistance to Ralstonia solanacearum - Fu, Huiwen; Zhuang, Yuhui; Zhang, Chong; Li, Shipeng; Zhang, Yongli; Lu, Wenzhi; Wang, Lihui; Abdullaziz, Sheidu; Chen, Yuting; Cai, Tiecheng; Yang, Qiang; Chen, Xiangyu; et al. (Frontiers in Plant Science, 2026)
Bacterial wilt, caused by Ralstonia solanacearum, is a destructive disease with no effective chemical control, severely affecting global crop production. This study applied BSR-seq on 581 recombinant inbred lines (RILs), combined with linkage mapping, to identify resistance quantitative trait loci (QTL). Illumina sequencing yielded 189.6 Gb of data, identifying 70,035 high-quality SNPs from 55,840 genes. Two resistance loci were mapped on chromosome 12: a novel 1.11 Mb QTL and an adjacent 1.03 Mb region. Five CC-NBS-LRR-type resistance candidate genes were identified. The AhRRS6 alleles were cloned, and three allele-specific SNP markers were developed and validated across peanut breeding varieties. Additionally, 3,851 differentially expressed genes were detected, including key resistance-related genes. Transgenic AhRRS6y conferred strong resistance to R. solanacearum, while AhRRS6x caused susceptibility in both Nicotiana benthamiana and Arabidopsis thaliana. These alleles differentially regulated genes in HR, ETI, and PTI pathways, particularly affecting NbPDF1.2 and NbNDR1. AhRRS6y expression reduced oxidative damage, indicated by lower malondialdehyde and higher ascorbate peroxidase activity. This work provides critical genetic resources for breeding bacterial wilt-resistant peanut varieties and enhances the mechanistic understanding of plant immune responses.